Restos a pagar de despesas com aç\~oes e serviços públicos de saúde da uni\~ao: Impactos para o financiamento federal do sistema único de saúde e para a elaboraç\~ao das contas de saúde - Fabiola Sulpino Vieira; Sérgio Francisco Piola (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The objective of this study is to analyze the impact of unpaid commitments by the central government on public healthcare financing and national health expenditure estimates. The health spending data were obtained from the federal public budget system, Siga Brasil, and were analyzed for their registration as unpaid commitments and canceled unpaid commitments from 2002 to 2014. We found that healthcare spending by the federal government was lower than the minimum level required by law for most years. As a result, approximately R 11.3 billion were not allocated to public healthcare by the federal government. As for health expenditure estimates, we found that the cancellation of unpaid commitments, among other issues related to national public accounting, affects the estimation of health spending by the accrual method, which is the recommended regimen in health accounts.
Keywords: H51; 330; government expenditures; public finance; public health